Tools of Radio Astronomy (Fifth Edition) - Wilson, Thomas L. (Springer, 2017)
Chapter 1: Radio Astronomical Fundamentals. Chapter 2: Electromagnetic Wave Propagation Fundamentals. Chapter 3: Wave Polarization. Chapter 4: Signal Processing and Receivers: Theory. (...)